Sports Perfectionism: Correlation of Individual Coping Behavior Strategies and Neurotic Disorders - Matiyeshyn, Ivan (Psychological Prospects Journal, 2015)
The article concretizes conceptual and methodological aspects of studying the phenomenon of sports perfectionism of personality. The basic aspects of the proposed research position of studying sports perfectionism in interrelation of manifestations of strategies of coping behavior and neurotic disorders of personality are outlined. The basic psychological peculiarities of sports perfectionism are defined, caused by the age and qualifying characteristics of sportsman, as well as readiness to react to the perfectionist demands of sports activity and formation level of personal maturity of sportsman. The constructive manifesta- tions of perfectionism are outlined, that are associated with positive attitude to activities, confidence in situations of competiveness and competitions and orientation on success; and destructive manifestations of sports perfectionism, that are shown in increasing intension of athletes, increase of anxiety, decrease of self-confidence and inclination to emotional burnout. The neurotic symptoms of destructive mani- festations of perfectionism of sportsmen are analyzed. The developed program of empirical research, as well as complex of used methods of mathematical processing of the results of the study, confirm the specificity of the manifestation of perfectionism, depending on the age range of the studied sportsmen. Sportsman aged from 15 to 18 years have socially determined perfectionism, accompanied by manifestation of aversive actions, moral normativity and frustration; perfectionism oriented on themselves have sportsmen aged from 18 to 25 years, accompanied by coping strategy of entering into social contact and neurotic rigidity; perfectionism oriented on others have sportsmen aged from 25 to 40 years, on the level of coping strategies, expressed by searching of social support and personal modesty. The general regularity of manifestation peculiarities of perfectionism of sportsmen is observed, through the determination of the effect of their self-presentation, shown in transformational signs of changes of coping strategies from frustration negativism to social acceptance.